PAYROLL ACCOUNTING SYSTEM DESIGN AND WAGE IN YOGYAKARTA GEA CRAF - Wardani, Mira Kurnia; Kholisoh, Dr. Luluk; Murdo,M.Si, Drs. Yuri (Accounting, 2010)
The purpose of this study was to determine how the implementation of Accounting System Payroll and Wage craf Gea has done so far. It also made the design of accounting systems appropriate Payroll and Wage Gea craf applied. Data collection was performed under the method of documentation, methods of interviewing and observation methods. Where in the method of documentation we do the recording and retrieval of data. The method of interview we conducted interviews in order to obtain information, testimony and statements from the leadership and employees involved in payroll and wages. The results of data collection indicate that the payroll and accounting system at Gea craf wage is still very simple and lack the necessary documents and calendar notes Gea craf highly vulnerable to fraud. And the need for payroll and accounting system design an appropriate wage to be implemented in craf Gea. Key words: accounting system, wage system